2023
DOI: 10.22159/ijap.2023v15i1.43571
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Activity of Volatile Compounds Derived From Pogostemon Cablin Benth as Antiviral of Sars-Cov-2

Abstract: Objective: Coronavirus disease-19 (COVID-19) is global pandemic which caused by SARS-CoV-2 infection. Mechanism of infection is initiated by attachment between viral glycoprotein with ACE2 receptor in human cells. Furthermore, Indonesia had a massive diversity of plants with a high potency of drugs, such as Pogostemon cablin Benth. In brief, it contained of various volatile compounds with many therapeutic properties. Therefore, this research aimed to identify the ability of volatile compounds from Pogostemon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…For a very long time, various plant parts, extracts, and sophisticated products had been utilized to treat illness. In summary, more than 50,000 higher plant species are thought to be utilized for therapeutic reasons worldwide [20][21][22][23][24] .…”
Section: Resultsmentioning
confidence: 99%
“…For a very long time, various plant parts, extracts, and sophisticated products had been utilized to treat illness. In summary, more than 50,000 higher plant species are thought to be utilized for therapeutic reasons worldwide [20][21][22][23][24] .…”
Section: Resultsmentioning
confidence: 99%
“…This interaction provides aromatic compounds that interact with single sulphur atom. 50 Sulphur gains specific function in biological activities consists folding stability and intermolecular interaction that larger than expected from vdw contacts. 51 Another research reported that S-arene interactions were preferred over O-arene ones due to the non-covalent bonds.…”
Section: Discussionmentioning
confidence: 99%